Exploring the diagnostic value of vestibular-evoked myogenic potentials in Multiple Sclerosis: a systematic review - Arunachalam Arunagiri Subramanian; Nirupama Siddaraju (The Egyptian Journal of Otolaryngology)
Abstract Vestibular-evoked myogenic potentials are neurophysiological tests that check the vestibular and the brainstem functions, but in most cases, both are affected by demyelination in multiple sclerosis. The conventional imaging techniques, most of the time, fail in detecting functional deficits, and in such cases, supplementary diagnostic tools are required. The aims of this review are to assess the sensitivity, diagnostic accuracy, and clinical implications of VEMP testing in detecting involvement of the brainstem in MS, to discuss whether it helps in diagnosing subclinical dysfunctions. For study selection, authors have conducted systematic review across PubMed, Scopus, and DOAJ databases. Twenty-one studies were included in this review, and selected studies evaluated the outcome latency, amplitude, asymmetry ratios, and the absent response in patients with multiple sclerosis as compared to the results reported from healthy controls. Results constantly showed that patients with MS had increased latencies, lower amplitudes, and greater asymmetry ratios, indicating that vestibular pathway was impaired in conduction by demyelination. VEMP proved useful in detecting subclinical dysfunction of the brainstem, where the MRI findings were normal, enhancing its diagnostic sensitivity. In addition to conventional imaging, VEMP provides functional abnormality that will necessitate very early intervention and monitoring over time as the disease unfolds. However, variability in study protocols and small sample sizes limit the generalizability of findings.